2015
DOI: 10.1002/stem.2048
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Faap20 Causes Hematopoietic Stem and Progenitor Cell Depletion in Mice Under Genotoxic Stress

Abstract: FAAP20 is a recently identified protein that associates with the Fanconi anemia (FA) core complex component, FANCA. FAAP20 contains a conserved ubiquitin-binding zinc-finger domain, and plays critical roles in the FA-BRCA pathway of DNA repair and genome maintenance. The function of FAAP20 in animals has not been explored. Here we report that deletion of Faap20 in mice led to a mild FA-like phenotype with defects in the reproductive and hematopoietic systems. Specifically, hematopoietic stem and progenitor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…To test the relevance of PrimPol function in response to ICLs in vivo , WT and PRIMPOL KO mice were treated with MMC, which rapidly depletes hematopoietic progenitor cells in the bone marrow (BM). MMC‐induced BM failure is exacerbated in strains deficient for FAN1, MUS81, SNM1, and FAAP20, all of which are required for ICL repair (Dronkert et al , 2000; McPherson et al , 2004; Dendouga et al , 2005; Zhang et al , 2015b; Thongthip et al , 2016). A dose of 7.5 mg MMC/kg of body weight was innocuous for WT mice and lethal only for a small percentage (20%) of KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…To test the relevance of PrimPol function in response to ICLs in vivo , WT and PRIMPOL KO mice were treated with MMC, which rapidly depletes hematopoietic progenitor cells in the bone marrow (BM). MMC‐induced BM failure is exacerbated in strains deficient for FAN1, MUS81, SNM1, and FAAP20, all of which are required for ICL repair (Dronkert et al , 2000; McPherson et al , 2004; Dendouga et al , 2005; Zhang et al , 2015b; Thongthip et al , 2016). A dose of 7.5 mg MMC/kg of body weight was innocuous for WT mice and lethal only for a small percentage (20%) of KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…The strong role for FAAP20 in HR and cell proliferation compared to FANCA elucidates repair mechanisms that can be preferentially utilized by dividing cancer cells. Other studies have shown that FAAP20 −/− mice have milder MMC sensitivity and greater amounts of colony formation in normal hematopoietic precursor cells than FANCA − / − mice 78 . This discrepancy emphasizes the influence of cell type when evaluating the importance of FAAP20’s repair roles and suggests the ability for selective therapeutic targeting of cancer cells over non-cancer cells by modulating FAAP20 activity.…”
Section: Discussionmentioning
confidence: 86%
“…FANCA, B, C, E, F, G and L, together with FAassociated protein 20 and 100 (FAAP20 and FAAP100), respond to genotoxic stress and are, in turn, recruited to the chromatin by FANCM, which is associated with FAAP24 and FANCM-interacting Histone-Fold protein 1 and 2 (MHF1 and MHF2) [43]. Although no FA patient has been identified thus far with mutations in FAAP20, FAAP24, FAAP100, MHF1 or MHF2, their inactivation in model organisms and/or cells resulted in a FA-like cellular phenotype, supporting their inclusion in the FANC group of proteins [44][45][46][47][48][49]. Assembled in the nucleus, the FANC core complex interacts with UBE2T, one of the most recently identified FANC gene (FANCT) [50,51].…”
Section: Fanconi Anaemia and The Fanc Genome Surveillance Pathwaymentioning
confidence: 98%